Role of Cyber Security in E-Learning Education - Bhoopendra Singh, Prof.(Dr.) Brijesh Kumar (International Journal of Advanced Science and Technology, 2020)
The exponential and demanding use of e-learning systems has become the prime and essential need of current education system. Despite of this enormous growth and usage of this e-learning system, The concern and attention regarding its security in Academics and Research to be adopted in day to day practice. Since the system are accessed and managed by the use of Internet over unlimited use of networks due to which the  e-learning systems has a unique challenge of its security concern. The major security threats and challenges involved in the security are such as hacking, phishing, unauthorized access, cracking, stealing sensitive information, and modification of data and configurations, as well as carrying out of academic misconduct incidents. As a representation and reports from various sources it has been revealed that the cyber security and its related attacks have increased at a very faster rate and significantly in recent past years. As a result, focusing the defensive measures in security, of accessed networks, hosts, applications, and Virtual private network (VPN) tunnels connect the independent networks, and user security to be properly defined in order to counter and avoid inadvertent attacks., IT policies, IT act , and specific guidelines in respect of  its procedure  related to security of e –learning management system  have become critical for any e-learning  organizations to prevent the major cyber attacks and to prevent further damage to the e-learning system.In this paper, the main focus is to define an easy approach to understand, explore, evaluate, and monitor the cyber security concerned to e-Learning systems. Moreover, this paper also lightens and brings out the various cyber-attacks due to absence of IT guidelines to be followed in security of e-Learning systems, in comparison of their defined security standard /architectureKeywords: Cyber threat, online e-Learning portal, cyber espionage, security -attack, security guidelines, VPN, dedicated networks.